2014
DOI: 10.1038/srep05978
|View full text |Cite
|
Sign up to set email alerts
|

p27kip1 haplo-insufficiency improves cardiac function in early-stages of myocardial infarction by protecting myocardium and increasing angiogenesis by promoting IKK activation

Abstract: p27kip1 (p27) is widely known as a potent cell cycle inhibitor in several organs, especially in the heart. However, its role has not been fully defined during the early phase of myocardial infarction (MI). In this study, we investigated the relationships between p27, vascular endothelial growth factor/hepatocyte growth factor (VEGF/HGF) and NF-κB in post-MI cardiac function repair both in vivo and in the hypoxia/ischemia-induced rat myocardiocyte model. In vivo, haplo-insufficiency of p27 improved cardiac func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…The results of the present study suggested that MSCs exert an antisenescence effect by triggering the secretion of VEGF, and that this effect is reduced by an anti-VEGFR2 antibody. Asa previous study found that H9c2 cells also express VEGF (33), the present study used RT-qPCR analysis to examine the mRNA level of VEGF in the H9c2 cells, however the results of the RT-qPCR analysis showed no difference between the H9c2 cells cocultured with MScs and H9c2 cells alone. The increase of free VEGF in the H9c2 MSc coculture may result from the MScs only.…”
Section: Discussionmentioning
confidence: 79%
“…The results of the present study suggested that MSCs exert an antisenescence effect by triggering the secretion of VEGF, and that this effect is reduced by an anti-VEGFR2 antibody. Asa previous study found that H9c2 cells also express VEGF (33), the present study used RT-qPCR analysis to examine the mRNA level of VEGF in the H9c2 cells, however the results of the RT-qPCR analysis showed no difference between the H9c2 cells cocultured with MScs and H9c2 cells alone. The increase of free VEGF in the H9c2 MSc coculture may result from the MScs only.…”
Section: Discussionmentioning
confidence: 79%
“…Our results suggest that IKKα is highly phosphorylated during cerebral ischemia-induced injury in pMCAO rats. IKK has been found to be activated in mouse/rat models of MCAO and myocardial infarction, although the associated mechanisms are obscure [1,30]. IKK phosphorylates NF-κB-bound IκBs and targets them for ubiquitin-dependent degradation, allowing the consequently liberated NF-κB dimers to Quantitative analysis of changes in Bcl-2 and Bax mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke is one of the most common causes of mortality and morbidity worldwide [1]. It has been proposed that brain cells experience a dramatic reduction in blood supply during an ischemic stroke; this reduction diminishes their access to oxygen and glucose and induces the pathophysiological features of damaged cells, thereby promoting necrotic cell death [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effect of p27 was mediated, at least in part, by activation of autophagy [243]. Interestingly, mice deficient in p21 or p27 have also been shown to be protected from some pathological conditions [244, 245]. This discrepancy may be explained by the fact that the mice used in these studies are germline knockout animals and thus many types of cells were affected instead of one single cell type.…”
Section: Cell Cycle Regulatorsmentioning
confidence: 99%